ANALISIS SWOT TERHADAP IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM OPTIMALISASI PENGELOLAAN PENDIDIKAN DI SD WIDIATMIKA - Ida Bagus Gede Surya Abadi; Chindytia; Desak Made Sri Udayani; Ni Made Ayu Candra Dewi (STKIP Subang, 2026)
School-Based Management (SBM) is an approach that grants schools autonomy in managing resources to improve educational quality. This study aims to analyze the implementation of SBM at SD Widiatmika and identify its strengths, weaknesses, opportunities, and threats using a SWOT analysis. This research uses a qualitative descriptive method, with data collected through observation, interviews, documentation, and analysis of the 2026 School Management Questionnaire. The results show that SBM at SD Widiatmika has been implemented very well, as all indicators across seven management components have been fulfilled: curriculum, student affairs, human resources, finance, facilities and infrastructure, public relations, and service quality. The SWOT analysis indicates several strengths, including effective school leadership, strong stakeholder support, a structured management system, and adequate facilities. Opportunities include technological development and strong community support. However, weaknesses remain in improving teachers’ digital competencies and maintaining consistent instructional innovation. Threats include changes in education policies and increasing demands for quality. Overall, SD Widiatmika has strong potential to optimize its management through innovation, collaboration, and adaptability to change.